قبل از بعثت عرب میں یہود کی آبادکاری اور ان کی سماجی حیثیت: The Jewish Settlement in Arabia before the Prophethood and their Social Status - Sajid Ali, Advocate Sajid Ali Chishti; Prof. Dr. Humayun Abbas (AL-IDRAK JOURNAL, 2024)
The Jews of Arabia held an ancient history, but they could not be considered the original inhabitants of the Arabian Peninsula. They migrated to this region at various times for different reasons and settled here. Over time, they established their influence and became an integral part of the society. Before the advent of Islam, they had already established significant populations in Arabia. In addition to industry and craftsmanship, they had excelled in agriculture and trade. The Arabs, on the other hand, were an illiterate nation with a mindset of idolatry, and the Jews, being the bearers of the Mosaic law and possessing ancient religious literature, had a significant impact on the Arabs. As a result, the Arabs would often seek their guidance in religious matters and considered them superior. Many Arab tribes had adopted Judaism, and many individuals had converted. Similarly, the Jews had also adopted Arab customs and traditions to assimilate with them. Their language, dress, and way of life had been influenced by Arab culture. They were considered part of the Arab nation, but despite this, they maintained their religious and intellectual identity, remaining steadfast to their beliefs.